1997
DOI: 10.1099/0022-1317-78-6-1357
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of pestiviruses from domestic and wild ruminants.

Abstract: Infections with pestiviruses occur in cattle, sheep, pigs and also in numerous other ungulate species. In the present study, pestiviruses from goat, buffalo, deer and giraffe were analysed at the molecular level ; unusual strains from cattle and pigs were also included. A phylogenetic analysis of the respective pestiviruses was undertaken on the basis of a fragment from the 5h noncoding region as well as the gene encoding autoprotease N pro . Statistical analyses of the respective phylogenetic trees based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
184
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(189 citation statements)
references
References 43 publications
0
184
0
4
Order By: Relevance
“…2,26,32,33 Some reports suggest that the 59-UTR region might not serve as an appropriate target sequence for phylogenetic analysis because of its highly conserved nature. 3 However, several investigators demonstrated that the 59-UTR region is suitable for subtyping BVDV isolates. 25,26,32 The 59-UTR region is efficiently amplified by RT-PCR and is the most frequently analyzed portion of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…2,26,32,33 Some reports suggest that the 59-UTR region might not serve as an appropriate target sequence for phylogenetic analysis because of its highly conserved nature. 3 However, several investigators demonstrated that the 59-UTR region is suitable for subtyping BVDV isolates. 25,26,32 The 59-UTR region is efficiently amplified by RT-PCR and is the most frequently analyzed portion of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Later, hybridization and more extensive sequence analysis revealed that the 5′NCR was highly conserved in BVDV genomes. This led to the suggestion that the 5′NCR region might not serve as a good target sequence for phylogenetic studies because of its highly conserved nature [5]. However, numerous investigators demonstrated that the 5′ NCR region provides a useful tool in genotyping BVDV isolates [6,32,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Early antigenic analysis revealed that ovine pestiviruses can be divided into two groups which include BDV-like and BVDVlike strains [11]. Recently, it has been demonstrated that ovine pestiviruses are divided into BDV, BVDV1 and BVDV2, both at the antigenic and genetic level [3,15,23,26]. The difficulty of distinguishing between the pestivirus genotypes and their ability to cross host-species barriers emphasise the value of laboratory typing of pestivirus strains.…”
Section: Introductionmentioning
confidence: 99%